Complete Sequence and Organization of pFR260, the Bacillus thuringiensis INTA Fr7-4 Plasmid Harboring Insecticidal Genes - Benintende, Graciela Beatriz; Berretta, Marcelo Facundo; Zandomeni, Ruben; Sauka, Diego Hernan; Amadio, Ariel F.; Ortiz, Elio Maximiliano; Navas, Laura Emilce (2017)
We report the complete sequence and analysis of pFR260, a novel megaplasmid of 260,595 bp from the Bacillus thuringiensis strain INTA Fr7-4 isolated in Argentina. It carries 7 insecticidal genes: 3 cry8 copies previously reported, 2 vip1, and 2 vip2 . Also, it carries a gene encoding a putative atypical Cry protein. These genes are arranged in a region of approximately 105 kbp in size with characteristics of a pathogenicity island with a potential coleopteran-specific insecticide profile. DNA strand composition asymmetry, as determined by GC skew analysis, and the presence of a Rep protein involved in the initiation of replication suggest a bidirectional theta mechanism of replication. In addition, many genes involved in conjugation and a CRISPR-Cas system were detected. The pFR260 sequence was deposited in GenBank under accession number KX258624.